La justice des mineurs au Québec : 25 ans de transformations (1960-1985) - Trépanier, Jean (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
This paper provides an overview of some of the changes undergone by the juvenile justice system in Quebec since 1960, with a particular attention to the evolution of its legal framework. Major legislative changes have stressed children's rights and diversion. The underlying philosophy of the law has been changed extensively, particularly concerning young offenders. Statistics reveal that the number of court referrals has increased considerably over time, and that diversion policies have been unable to change this trend. Juvenile court dispositions seem to show a greater degree of intervention than before.